Determinants of Employees’ Engagement in Airline Companies Based in Malaysia - Burhanuddin, Mohd Nazrin; Osman, Zahir; Raju, Valliappan (International Journal of Economics, Business and Management Studies, 2020)
The aim of this study is to investigate the direct effect of employees’ satisfaction, working environment, teamwork and employees’ engagement relationship in Malaysian airlines companies in Malaysia. To analyse the causal relationships among employees’ satisfaction, working environment, teamwork and employees’ engagement, the Structural Equation Model (SEM) was adopted. The model utilizes Partial Least Square (PLS) procedure on data collected from a survey that yielded 226 usable questionnaires. The results showed that employees’ satisfaction, working environment and teamwork enhance employees’ engagement in Malaysian airlines companies in Malaysia. It is vital to do the research utilizing experimental design by using longitudinal data in Malaysian airlines companies via vigorous measures. The findings suggest that the airlines companies must put emphasis on employees’ satisfaction, working environment and teamwork to ensure the effective increase in airlines employees’ engagement at their workplace. This research is one of the first known efforts to use employees’ satisfaction, working environment and teamwork to study employees’ engagement in airlines sector in Malaysia by using Partial Least Square (PLS) procedure.